Comparative Analysis of Two Surgical Treatment Options for Giant Cell Tumor of the Proximal Femur: Extended Curettage and Segmental Resection - Yuan, Yuhao; Liu, Qing; Liu, Yupeng; Wu, Ziyi; Zhong, Wei; He, Hongbo; Luo, Wei (Frontiers in Oncology, 2021)
Aim ：This study aimed to compare the differences in local recurrence, reconstruction durability, and postoperative function after treatment with either extended curettage (EC) or segmental resection (SR) for giant cell tumor of the bone (GCTB) in the proximal femur so as to provide constructive suggestions for rationalization of surgical options. Patients and Methods:29 patients (15 men and 14 women) were included in this study, with a mean age of 32.1 years. According to the division method of proximal femur of International Society Of Limb Salvage (ISOLS), there was 1 case in the H1 area, 17 cases in the H2 area, 10 cases in the H1+H2 area, and 1 case in the H1+H2+H3 area. Among them were 11 cases of Campanacci grade II GCTB, 18 cases of Campanacci grade III GCTB, and 7 cases with pathological fractures. All patients underwent either EC or SR surgery. The Musculoskeletal Tumor Society (MSTS) score was used for patient evaluation. Regular follow-up was performed to evaluate the recurrence rate, limb function, and long-term complications of the two surgical methods. Results:All patients were followed up for a mean of 60.4 months. Local recurrence occurred in one of 19 patients treated with EC (5.3%) and one of 10 patients treated with SR (10%). The MSTS score of lower limb function in patients in the EC group was better compared to patients in the SR group (P = 0.002). Complications occurred in 2 cases (10.5%) and 5 cases (50%) in the EC group and SR group, respectively, with significant differences between the two groups (P = 0.03). The operation effectiveness was analyzed according to the Mankin evaluation standard. The EC group showed an optimal rate of 94.7% (18/19) as opposed to 80% (8/10) in the SR group. Conclusions：For GCTB in the proximal femur, as long as the articular surface is complete and there is no pathological fracture with apparent displacement, EC should be fully considered as the preferred treatment of choice.